Granulocyte and monocyte adsorption apheresis for Behçet's disease in a pregnant woman. Issue 12 (4th December 2013) - Higashi, Yuko; Shimokawa, Mitsuyoshi; Kawai, Kazuhiro; Kanekura, Takuro
Abstract We present a 39‐year‐old pregnant woman with Behçet's disease who was treated successfully with granulocyte and monocyte adsorption apheresis (GMA). There were no complications or adverse effects during her pregnancy and delivery. The neonate manifested no abnormalities.